Contextualiser pour didactiser : le copier-coller dans le champ des littératies universitaires - Fanny Rinck (Corela)
The practice of copy and paste among students is equated with plagiarism and the institutional response is devoted to “discipline and punish”. However this practice is an important issue within the framework of academic literacies, in relation to the necessary consideration of the digital literacy. The fact that it is conceived as a "misconduct" from an ethical point of view is to be understood with regard to a normative frame that calls for academic honesty and establishes the author and the sources as essential components of research writings, without much explaining the issues (why? how? etc.). How to think copy and paste and what to do? How to go from the state of unacceptable to a didactic view, and what to take into account? With the prospect of critical reflexivity in the field of academic literacies, we propose some elements of contextualization which make it possible to problematize copy and paste, as a gesture of writing, as an object of debates, and in order to better prepare students with academics expectations and in terms of literacy skills in general. We develop first the way copy and paste is received, then the fact of writing by copy and paste, and finally the tension and confusions around expectations related to students' writings. Context is understood here as an interpretative framework that serves a didactic approach as such.